Design of a 1×2 CPW Fractal Antenna Array on Plexiglas Substrate with Defected Ground Plane for Telecommunication Applications - Ben Nsir, C.; Ribero, J. M.; Boussetta, C.; Gharsallah, A. (Engineering, Technology & Applied Science Research, 2021)
In this paper, a fractal antenna array for telecommunication applications is presented. The proposed antenna array is realized on a Plexiglas substrate, has 1×2 radiating elements, and dimensions of 170mm×105mm. The antenna array is composed of two Koch Snowflake patches and is fed by a Coplanar Waveguide (CPW) transmission line. Radiating elements and the ground plane are printed on the top side of the substrate. Defected Ground Structure (DGS) technique is employed to enhance the bandwidth and improve the impedance matching. The proposed antenna array operates at two frequency bands, 1.08-1.32GHz covering the GPS band and 1.7-3.7GHz covering the GSM 1800/1900, UTMS, Bluetooth, LTE, and WiMAX bands. In addition, the antenna has a good performance with efficiency and peak gain of 82% and 6.3dB respectively. These characteristics allow the antenna to be an attractive candidate for telecommunication systems. Design and analysis of different structures were carried out with Ansys HFSS.